THE IMPLEMENTATION OF SCIENTIFIC MULTILITERACIES EDUCATION IN ENHANCING STUDENTS’ CRITICAL THINKING SKILLS IN SOCIAL STUDIES IN ELEMENTARY SCHOOL: A SYSTEMATIC LITERATURE REVIEW - Eva Nesa Lia Eva; Efi Yulyana; Ahmad Sheca Rahmadi (Journal of Pedagogical Content Knowledge, 2026)
This study aims to analyze the implementation of scientific multiliteracy learning in enhancing students’ critical thinking skills in social studies at the elementary school level. The research method used was a systematic literature review, examining various relevant previous studies. The data sources for this study were national and international journal articles published between 2018 and 2024. The results of the study indicate that the implementation of scientific multiliteracies instruction has a positive effect on improving the critical thinking skills of elementary school students in social studies. This is evidenced by improvements in students’ ability to analyze information, solve problems, and make evidence-based decisions. The scientific multiliteracies approach also helps students develop the digital literacy, visual literacy, and information literacy skills necessary in the digital age.